ANALISIS PROFIL SOSIAL EKONOMI PEDAGANG SAYUR LESEHAN DI PASAR TRADISIONAL (Studi Kasus : Pasar Tradisional Kemiri Kecamatan Medan Kota, Kota Medan) - FAOEZA HAFIZ SARAGIH, KIKI CENDIKIA SINAGA, ZULKARNAIN LUBIS, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2019)
Market was an important things in economic especially traditional market, which many vegetable street vendors sell in this market everyday. Every single of them have to pay many cost meanwhile the vegetable which they sell was cheap. The aim of this research to know the profile of the vegetable street vendors in the traditional market of Kemiri, Medan Kota District, Medan City. This research used structured interview methods and in-depth interviews. The number of samples of vegetable street vendors was 10 sample. The results showed that trade income was enough for daily expenses, the education of vegetable street vendors children was fulfilled, all vegetable traders had decent house and all vegetable traders had good health. However, there’s something have to noticed they don’t have of legal certainty in trading, the widespread practiced of illegal levies, there’s absences of training and assistance from the government in trading, and social interaction with neighbors who have never been carried out.Keywords : Vegetable, Street Vendor, Traditional Markets, Social, Economic.